Redesign of Constitutional Ethics For State Administrator Based on The Value of Pancasila - Muhtadi Muhtadi; Indra Perwira (Universitas Lampung, 2018)
A constitution is a collective agreement as the foundation and goal to be achieved in the state. Therefore, the constitution not only regulates the fundamental rules of the state but also contains the ethical values that serve as the guiding of the state administrator. However, the spreading of violations of law such as corruption, abuse of authority that ends in the imposition of sanctions justifies the occurrence of incompatibility between the values of the constitutional principle as a reflection of the soul of the nation with the moral obligation of state administrator to implement the values. Using a doctrinal approach, data will be analyzed through the original intent of interpretation, grammatical and systematic law is expected to formulate a new model of constitutional ethics for state administrator based on the value of “Pancasila.” Based on the study of moral and constitutional philosophy with the law interpretation method can be concluded that the ethical values in the 1945 Constitution requires that state administrator base their deeds on the moral deity who respects the values of human civilization as Indonesian citizens, and humans in general with the priority of Indonesian unity above all interests and classes in order to achieve the ideals of social justice based on a deliberate-oriented on the great goal of Indonesian independence. To achieve this intention, the formation of ethical standards of the administrator in the constitutional norms through the amendment of the 1945 Constitution which then set a further law which is general and contains normative sanctions. Keywords: Redesign, Constitutional Ethics, State Administrator